TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PERSEROAN OLEH PERUSAHAAN CHANDRA ASRI PACIFIC TERBUKA DI WILAYAH CILEGON PROVINSI BANTEN: Corporate Social and Environmental Responsibility by Chandra Asri Pacific Public Company in Cilegon Area Banten Province - Hana Muthiah Salsabilah; Sri Bakti Yunari (Reformasi Hukum Trisakti, 2025)
Social and Environmental Responsibility of the Company as stipulated in Article 74 of Law Number 40 of 2007 concerning Limited Liability Companies, in its application there are many obstacles, including Social and Environmental Responsibility carried out by PT Chandra Asri Pacific Tbk. The main problems discussed, whether the implementation of social and environmental responsibility by PT Chandra Asri Pacific Tbk is in accordance with Indonesian laws and regulations, and what are the obstacles in the implementation of social and environmental responsibility. The research method in this study uses normative research type and uses secondary data support through literature study and interviews, qualitative analysis is carried out with deductive conclusions. The results and conclusions of this article are the implementation of Social dan Environmental Responsibility carried out by PT Chandra Asri Pacific Tbk has been implemented through various programs both in the social and environmental field, in practice there are also obstacles in the implementation of Social and Environmental Responsibility by PT Chandra Asri Pacific Tbk, namely in the form of juridical and non-juridical obstacles.